Factors associated with intraoperative intravenous catheter extravasation in children. Issue 4 (July 2022) - Mecoli, Marc D; Ding, Lili; Yang, Gang; McSoley, Joseph W; Doellman, Darcy A; Rineair, Sylvia A; Subramanyam, Rajeev
Summary: This retrospective study aimed to determine the incidence of and factors associated with peripheral intravenous extravasation in paediatric patients in the intraoperative setting. We conducted a retrospective study of 56, 777 patients who underwent general anaesthesia and had peripheral intravenous catheter placement at Cincinnati Children's Hospital between 1 January 2015 and 1 January 2017. Data collected included age, American Society of Anesthesiologists Physical Status Classification, catheter site, number of cannulation attempts, ultrasound use for cannulation, surgery duration, and surgery class. Primary outcome was peripheral intravenous extravasation using an extravasation assessment tool. Some 64, 814 peripheral venous catheters were placed in patients undergoing general anaesthesia. Significant extravasation was documented in 40 catheters with an estimated incidence of 1 in 1620 venous catheters (0.06%). Of those 40 catheters, 47.5% ( n = 19) were placed using ultrasound and 37.5% ( n = 15) required more than one cannulation attempt. In multivariable analysis, peripheral intravenous catheter extravasation was associated with American Society of Anesthesiologists Physical Status Classification (3, 4, 5) versus (1, 2) (odds ratio 2.42 (95% CI 1.08 to 5.41)), inpatient versus outpatient surgeries (odds ratio 2.99 (95% CI 1.31 to 6.81)), and intravenous catheters placed with ultrasound guidance (odds ratio 8.01 (95% CI 4.12 to 15.57)). Our study identified factors associated with intraoperative peripheral intravenous extravasation, and will help develop mitigation strategies to minimise harm to patients.